Modelling of Nonlinear Magnetic Properties of Current Transformers with Piecewise Bézier Curves - Rahmanović, Ermin; Kerndl, Matej; Polajžer, Boštjan; Černelič, Jernej; Petrun, Martin (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The magnetic properties of iron cores of contemporary electrical devices, such as current transformers, are highly nonlinear. This work proposes a simple modelling method for the nonlinear magnetic properties using piecewise Bézier curves. An anhysteretic curve is modelled with three measured points. Two second order Bézier curves are joined to form a composite curve based on those measured points. The modelled curve was then compared with a measured anhysteretic curve of a commercial electrical steel sheet. The presented results confirm that this approach with piecewise Bézier curves shows high potential to model magnetization curves.